Coordinated droop control for distributed generation in microgrids - Zhang, Yufei (2017)
Microgrid is an autonomous system which can achieve self control, protection and management. The purpose of microgrid is to realize the flexible and efficient application of distributed power supply, and to solve the problem of large number of grid connected distributed generation. The parallel inverters control system based on droop control has good redundancy, simple connection, and the system is easy to build. In this paper, an advanced droop control is designed to coordinate multiple distributed generation systems in microgrids and current sharing effect is studied by simulating the Matlab/Simulink Model. Also, the transition between grid connection operation and independent operation is explored. In general, this paper present the effect of PQ droop control, including PR and P controller in double closed loop. The conclusion is that after using droop control, the current sharing effect can be improved especially on the reactive power sharing. Seamless transition between grid-connected mode and islanded mode is also achieved in this paper. Key words: PQ droop control; parallel inverter; PR controller; Seamless transition